Clinical and epidemiological profile of patients with valvular heart disease admitted to the emergency department - Moraes,Ricardo Casalino Sanches de (2014)
Objective To evaluate the clinical and epidemiological profile of patients with valvular heart disease who arrived decompensated at the emergency department of a university hospital in Brazil.Methods A descriptive analysis of clinical and echocardiographic data of 174 patients with severe valvular disease, who were clinically decompensated and went to the emergency department of a tertiary cardiology hospital, in the State of São Paulo, in 2009.Results The mean age of participants was 56±17 years and 54% were female. The main cause of valve disease was rheumatic in 60%, followed by 15% of degenerative aortic disease and mitral valve prolapse in 13%. Mitral regurgitation (27.5%) was the most common isolated valve disease, followed by aortic stenosis (23%), aortic regurgitation (13%) and mitral stenosis (11%). In echocardiographic data, the mean left atrial diameter was 48±12mm, 38±12mm for the left ventricular systolic diameter, and 54±12mm for the diastolic diameter; the mean ejection fraction was 56±13%, and the mean pulmonary artery pressure was 53±16mmHg. Approximately half of patients (44%) presented atrial fibrillation, and over one third of them (37%) had already undergone another cardiac surgery. Conclusion: Despite increased comorbidities and age-dependent risk factors commonly described in patients with valvular heart disease, the clinical profile of patients arriving at the emergency department represented a cohort of rheumatic patients in more advanced stages of disease. These patients require priority care in high complexity specialized hospitals.